2011
DOI: 10.1007/s00330-011-2135-1
|View full text |Cite
|
Sign up to set email alerts
|

Dual energy CT pulmonary blood volume assessment in acute pulmonary embolism – correlation with D-dimer level, right heart strain and clinical outcome

Abstract: Pulmonary blood volume on DECT in acute PE correlates with RHS and appears to be a predictor of patient outcome in this pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 34 publications
(41 reference statements)
2
59
0
4
Order By: Relevance
“…In addition, the numbers of lobes with pulmonary perfusion defects on iodine images of DECTA correlated well with RV/LV diameter ratio (r = 0.66, p < 0.05), whereas the number of lobes with PE on CT angiography did not (p > 0.05). Quantification of the area of pulmonary perfusion defect on iodine images showed that an pulmonary perfusion defect over 215.4 ml or a relative volume over 9.9% was related to an RV/LV diameter ratio > 1 (Bauer et al, 2011). These results therefore indicate that pulmonary perfusion defect size may be a surrogate marker for RV dysfunction (Fig.…”
Section: Dual E Ctmentioning
confidence: 64%
See 2 more Smart Citations
“…In addition, the numbers of lobes with pulmonary perfusion defects on iodine images of DECTA correlated well with RV/LV diameter ratio (r = 0.66, p < 0.05), whereas the number of lobes with PE on CT angiography did not (p > 0.05). Quantification of the area of pulmonary perfusion defect on iodine images showed that an pulmonary perfusion defect over 215.4 ml or a relative volume over 9.9% was related to an RV/LV diameter ratio > 1 (Bauer et al, 2011). These results therefore indicate that pulmonary perfusion defect size may be a surrogate marker for RV dysfunction (Fig.…”
Section: Dual E Ctmentioning
confidence: 64%
“…7). Readmission and death due to PE were observed only in patients with a relative perfusion defect size >5% of total lung volume, but not in any patient with a relative perfusion defect < 5% (Bauer, Frellesen et al 2011). Patients with a relative perfusion defect >5% also showed lower median survival with increased relative hazard ratio for death than those with a relative perfusion defect <5%.…”
Section: Dual E Ctmentioning
confidence: 86%
See 1 more Smart Citation
“…Right heart strain (RHS) has been shown to be independently predictive of 30-day mortality. In addition to use as a CT marker of RHS, the ratio between the size of the right ventricle (RV) and left ventricle (LV) has demonstrated a significant positive correlation with severity of PE and mortality Bauer RW, 2011] also reported that looking at the incidence of readmission and death due to PE demonstrated these major hard endpoints only in patients with a relative PD size of >5% of the total lung volume, whereas no such event was recorded for patients with <5% RelPD (relatively to the total lung volume, RelPD). Median survival time, however, was significantly lower for patients with >5% RelPD at an increased relative hazard ratio for death compared to patients with <5% RelPD or the control group without PE.…”
Section: Evaluation Of Pe Severitymentioning
confidence: 99%
“…Radionucleotide perfusion or ventilation ⁄ perfusion scans and pulmonary magnetic resonance angiography are all reasonable alternatives in ambulant patients, but not in haemodynamically unstable or ICU patients receiving controlled ventilation. In addition to merely detecting or excluding the presence of PEs, CTPA can be used to quantify the pulmonary clot burden [32,33] and the extent of RV dysfunction (using four chamber reconstruction views RV:LV diameter ratio [31] or volumetric analysis [33]). Neither of the current pre-CTPA, PE prediction tools [1] is useful or validated in the peri-operative and ICU patient populations [34].…”
Section: Definitive Imagingmentioning
confidence: 99%